2008
DOI: 10.1074/jbc.m806786200
|View full text |Cite
|
Sign up to set email alerts
|

Mesodermal Deletion of Transforming Growth Factor-β Receptor II Disrupts Lung Epithelial Morphogenesis

Abstract: In vertebrates, Sonic hedgehog (Shh) and transforming growth factor-␤ (TGF-␤) signaling pathways occur in an overlapping manner in many morphogenetic processes. In vitro data indicate that the two pathways may interact. Whether such interactions occur during embryonic development remains unknown. Using embryonic lung morphogenesis as a model, we generated transgenic mice in which exon 2 of the T␤RII gene, which encodes the type II TGF-␤ receptor, was deleted via a mesodermal-specific Cre. Mesodermal-specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
0
31
1
Order By: Relevance
“…Knockout of transforming growth factor β receptor II, a receptor for TGFβ ligands that is involved in epithelial-mesenchymal communication during development, causes cystic lung with defective branching (115). Interestingly, the Hh signaling transcriptional targets Ptch1 and Gli1 were increased without altered Shh expression, suggesting the possibility of non-canonical pathway regulation.…”
Section: Lessons From Functional Inhibition and Overexpression Of Hh mentioning
confidence: 96%
“…Knockout of transforming growth factor β receptor II, a receptor for TGFβ ligands that is involved in epithelial-mesenchymal communication during development, causes cystic lung with defective branching (115). Interestingly, the Hh signaling transcriptional targets Ptch1 and Gli1 were increased without altered Shh expression, suggesting the possibility of non-canonical pathway regulation.…”
Section: Lessons From Functional Inhibition and Overexpression Of Hh mentioning
confidence: 96%
“…35 Interactions between TGF-␤, Shh, Wnt, FGFs, and BMPs have been described at multiple levels, both in normal lung development, remodeling, and disease. [114][115][116][117] Because of their importance in both lung development and remodeling, and likely also the development of BPD, regulatory molecules of these pathways may be of special interest for the development therapeutic interventions for BPD. 35,83,84 CTGF, for example, can induce Wnt-signaling, reciprocally switch on Smad signaling, and inhibit VEGF.…”
Section: Wwwajogorgmentioning
confidence: 99%
“…Previous studies have shown that conventional deletion of TβRII leads to early embryonic lethality (11), while mesenchymal deletion of TβRII results in gross abnormalities of trachea and lung (16). To study the role of TβRII specifically in lung epithelial cells, we crossed TβRII fl/fl females with Nkx2.1-cre male mice and backcrossed the heterozygotes to generate TβRII fl/fl ;Nkx2.1-cre (simply, TβRII Nkx2.1-cre ) progeny.…”
Section: Epithelial Inactivation Of Tβrii By Nkx21-cre-driven Recombmentioning
confidence: 99%